Statins and the incidence of post-stroke depression: a systematic review and meta-analysis - Cui, Chaohua; Li, Jue; Chen, Weicong (Frontiers in Neurology, 2025)
IntroductionPost-stroke depression (PSD) can lead to poorer functional outcomes and prognosis. Brain inflammation is a risk factor for PSD. Statins might be beneficial due to their anti-inflammatory properties. Different studies have yielded varying results regarding the effects of statins. Therefore, this meta-analysis aims to clarify the effect of statins on PSD.MethodsObjectives: To evaluate the relationship between PSD and the use of statins. Data Sources: Databases including PubMed, Web of Science, Embase, and Cochrane Library. Eligibility Criteria: Original observational cohort studies. Participants: Patients with ischemic stroke. Interventions: Use of statins. Appraisal and Synthesis Methods: Forest plot to display pooled results; I2 test to evaluate heterogeneity.ResultsOf the 37 studies selected, four were eligible. The four studies included 93,893 patients (with statins: 45,598) and more than 17,470 PSD patients. The mean age ranged from 62.1 to 70.8 years. The percentage of female participants ranged from 42.1% to 57.9%. For PSD in different regions, the pooled OR for all regions using random-effects methods was 1.21 (95% CI: 0.44–3.33). The pooled OR for Asian populations was 1.42 (95% CI: 0.37–5.40), and for European populations, it was 0.76 (95% CI: 0.73–0.78). The pooled OR for all regions using fixed-effects methods was 0.84 (95% CI: 0.81–0.86). The pooled OR for Asian populations was 2.62 (95% CI: 2.34–2.93).ConclusionDepending on the pooling method used, statin use in Asia either increased or had no relationship with PSD. For European patients, statin use reduced the incidence of PSD.